Thermal Diffusivity Measurement and Photobleaching Study Using Photoacoustic Technique and UV –Visible Fibre Optics Spectrometry - Chan, Kok Sheng (2002)
In recent years, the photoacoustic effects in solid materials, induced by the absorption of intensity-modulated laser radiation, were used as a versatile tool for optical and thermal characterization of a variety of samples. In our work, by using the photoacoustic detection technique, the measurement was first carried out to obtain the thermal diffusivity values of commercial papers (i.e. white paper, drawing paper, filtering paper, wrapping paper, fax paper and press paper), sago starch, chitosan and the blends of sago starch with chitosan. All the measurements for these samples were carried out at room temperature. It was based upon the measurement of the photoacoustic signal as a function of the modulation frequency in the region where the thermal diffusion length equals to the sample thickness.